Graft Arterial Stenosis in Kidney En Bloc Grafts From Very Small Pediatric Donors: Incidence, Timing, and Role of Ultrasound in Screening. Issue 11 (7th July 2015) - Bent, C.; Fananapazir, G.; Tse, G.; Corwin, M. T.; Vu, C.; Santhanakrishnan, C.; Perez, R. V.; Troppmann, C.
<x xml:space="preserve">Abstract</x> In previous studies with different donor selection criteria and noncontemporary surgical techniques, graft arterial stenosis (GAS) has been reported to occur more frequently in adult recipients of pediatric en bloc renal allografts (EBKT) as compared to single adult donor allografts. The purpose of our study was to evaluate the incidence of GAS within our EBKT recipient population and to evaluate clinical and imaging features of those cases with GAS. In a retrospective cohort study, we analyzed 182 EBKT performed at a single institution. We identified cases of suspected GAS based on clinical factors, lab results, and noninvasive imaging. Diagnosis of GAS was confirmed by digital subtraction angiography. Two EBKT recipients (1.1% of 182) had angiographically confirmed GAS at 2.5 and 4.5 months after transplant. In both cases, the stenoses were short segment within the proximal (perianastomotic) donor aorta, color Doppler ultrasound demonstrated peak systolic velocities of >400 cm/s, and poststenotic parvus tardus waveforms were present. Both patients underwent angioplasty and demonstrated postintervention improvement in renal function and blood pressure. Restenosis did not occur during follow up. In conclusion, recipients of EBKT have a low incidence of GAS, similar to the lowest reported for adult single allografts.